Antimicrobial potential of Pediococcus acidilactici from Bekasam, fermentation of sepat rawa fish (Tricopodus trichopterus) from Banyuasin, South Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Melia S, Purwati E, Kurnia Y. F, Pratama D. R. 2019. Antimicrobial potential of Pediococcus acidilactici from Bekasam, fermentation of sepat rawa fish (Tricopodus trichopterus) from Banyuasin, South Sumatra, Indonesia. Biodiversitas 20: 3532-3538. This study aimed to determine the antimicrobial potential of lactic acid bacteria isolated from bekasam. Bekasam is a result of sepat rawa fermentation from Banyuasin District, South Sumatra, Indonesia. The results showed that the morphological and biochemical properties of lactic acid bacteria were Gram-positive and cocci, negative catalase and included in homofermentative groups. The biggest antimicrobial activity was shown by bekasam isolate to Escherichia coli O157: H7 (21.26 mm), followed by Staphylococcus aureus ATCC25923 (18.23 mm) and Listeria monocytogenes CFSAN004330 (5.10 mm), while diameter barriers for crude bacteriocin supernatant isolates lactic acid bacteria to Escherichia coli O157: H7, Staphylococcus aureus ATCC25923 were 14.99 mm, 17.69 mm, and Listeria monocytogenes CFSAN004330 had no antimicrobial activity at neutral pH. The results of molecular identification with 16S rRNA showed that lactic acid bacteria isolated from bekasam isolate have similarity with Pediococcus acidilactici strain PB22 that has antimicrobial potential against pathogenic bacteria and potential as bio preservatives.
Keywords: Antimicrobial, bekasam, fermented fish, lactic acid bacteria, sepat rawa